Studi Kelayakan Pembangunan Pabrik Krim Anti-Aging Berbahan Dasar Kunyit dan Daun Asam - Rachman, Alfajriyanti; Satriawan, I Ketut; Suwariani, Ni Putu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2022)
Feasibility study for development of a factory is an analytical system that is used as a consideration for accepting or rejecting a planned business idea/project. Turmeric and tamarind leaves are potential as anti-aging skin. The feasibility study for the factory construction was carried out with 4 aspects, namely market aspects, technical aspects, management and human resources aspects, and financial aspects with an analysis period of 5 years. The results of the analysis are viewed from the market aspect, namely market segmentation with criteria for women aged 25 to 64 years and has a chance of 10.2%. Technical aspects, with the best factory location in Denpasar. Aspects of management and human resources, have an organizational structure with sufficient manpower. Financial aspects, NPV Rp 7,428,003,201, IRR 34.90%, BC Ratio of 1.28, PBP for 3 years 3 months, BEP units 105.752,74 and BEP price Rp 5.499.142.445 also sensitivity analysis shows that the anti-aging cream business of turmeric and tamarind leaves is still financially feasible if there is a decrease in production up to 10%. . Keywords : Feasibility, anti-aging cream, tumeric, tamarind leaves